Hello :
<span>3y = x + 6 ...(1)
y – x = 3...(2)
by (2) : y = x+3...(*)
subsct in (1) :
3(x+3) = x+6
3x-x= -9+6
2x= -3
x=-3/2
subsct in (*) : y =-3/2 +3 =3/2</span>
Answer:
-3x= 2×2-4
Step-by-step explanation:
-3x= 4-4
-3x= 0
divide both sides by the co-efficient of x
-3x/-3= 0÷-3
x = 0
Answer:
The solution is (-2, 4)
Step-by-step explanation:
When finding the solution of system of equations, you need to find where both lines intersect.
In the graph shown, the light purple and dark purple line meet at (-2, 4).
Hope this helps!!
It’s 182 my work is in the picture